Clinical aspects of a large group of adults with Angelman syndrome. Issue 1 (27th October 2020) - den Besten, Inge; de Jong, Rianne F.; Geerts‐Haages, Amber; Bruggenwirth, Hennie T.; Koopmans, Marije; ,; Brooks, Alice; Elgersma, Ype; Festen, Dederieke A. M.; Valstar, Marlies J.
Abstract: Descriptions of the clinical features of Angelman syndrome (AS) have mainly been focused on children. Here, we describe the evolution of the clinical phenotypes of AS in adulthood, using clinical data from 95 individuals (mean age 31.6 years, median 29.0 years, range 18–83 years), with genetically confirmed AS. Data was collected through physical examination and inspection of medical records, combined with questionnaires and interviews. Adults with AS experience substantial debilitating health problems. Constipation, reflux, visual problems, scoliosis, behavioral and sleeping problems occurred frequently and require appropriate attention. Epilepsy was reported in 57% of adults, negatively affecting the level of functioning. Non‐convulsive status epilepticus was not observed in the adults, however some individuals developed prolonged episodes of rhythmic shaking while awake. A decline in mobility was noted in the majority of adults. A minority of adults with AS showed microcephaly. Taken together, this first phenotypic study of adults with AS to include in person interviews with care‐givers and physical examination of patients, including the eldest adult reported to date, provides important insight in the development of the syndrome into adulthood. This knowledge is required to improve care for adult individuals with AS and to evaluate future therapies for this group.